Analysis of students' writing ability using concept maps based on Dienes’ theory - Alfiani Athma Putri Rosyadi; Yus M. Cholily; Dini Okta Amelia; Shilviana Dwi Fitdyawati (Universitas Muhammadiyah Malang, 2025)
As one of the important aspects in learning, both written and oral, communication is obtained from how students express their ideas. One of them is by using a concept map that is compiled using relevant theoretical references. Dienes’ theory can connect students' ideas with other appropriate concepts and theories. The purpose of this study was to describe the process of students' written communication using concept maps and based on Dienes’ theory. This descriptive qualitative study used instruments in the form of test sheets and interviews. The results of the study showed that students' written communication based on the aspect of mathematical communication using concept maps was in the high category. This shows very good abilities in various aspects, including clarity of delivery, completeness of solution, use of mathematical models, interpretation of results, and mathematical communication. However, the results of the analysis of students' answers from the low category showed that their mathematical communication skills needed improvement in the aspect of conveying ideas. Suggestions for further research are to bring up aspects of conveying ideas that can be combined with open-ended questions. In addition, the steps of Dienes’ theory can be combined with problem-based learning that brings up the process of communicating students' ideas in writing and orally.